An Industrial Quality Control Study on Relay Electronics Manufacturing, Corp. - Luy, Don Mark; Salvatiera, Michelle Ray.; Ventura, Jonathan (Diliman, Quezon City College of Engineering, 2001)
Today, quality is set by the customer. It is meeting and exceeding the customer's expectations and needs. Quality sounds simple, but only the best companies around the world are making these things happen on a daily basis. The objective of the study is to apply the framework of the basic philosophy and and principles of statistical process control in a real-world production system. Relay electronics is a manufacturer of emergency lighting systems, fire alarms, burglar alarms, and PA sound systems. The study focuses on the product which contributes most to the sales revenue of the company, emergency lights and its production process. The researchers documented the existing production process and quality procedures including sampling and inspection plans from raw materials acquisition, work-in-process to finished goods. A process map provides a summary of processes including quality control points and their corresponding checkpoint. Failure modes, effects and criticality analysis was done on a functional level so as to identify critical product failures. After identifying PCB failure as critical, a hardware level FMECA was done to identify critical circuit board components such as relays, diodes and transistors. Major quality problems for the company were identified as follows: 1. Absence of a standardized acceptance sampling plan for raw materials, 2. No records of quality performance indicators such as rework and scrap rates , and 3. No process control of PCB production at testing stage. Problem analysis tools were used to verify failures found to be critical in an FMECA and to find causes for these failures. Prioritization was done and it was found that relays constitute the greatest amount of rework done at this station.
From the process map, control stations are identified and on-line control charting was applied to key parameters related to performance of the critical components. Control charting was done on the cut-off voltages and the initial charging current, all of which are parameters related to the automatic charging of emergency lights. Based on the control charts, cut-off voltage and initial charging current were found to be in-control. Next, process capability analysis was done to determine if the process is capable of meeting the specifications set by the design engineer. The process was found to be incapable of meeting the specifications of the battery cut-off voltage due to unreliable relays. Then, a quality cost analysis was done for proposed acceptance sampling plans. Furthermore, costs were evaluated for implementing a process improvement by acquiring a better performing relay so as to reduce the rework and to meet the specifications for battery cut-off voltage. Moreover, the quality costs related to documentation and its advantages in implementing a successful quality program were highlighted. The recommendations of the study are: 1. To implement statistical process control charting at the PCB testing stage so as to monitor valuables related to critical parameters. The method of implementation and the aspects of control charting strategy such as the choice for limits and sampling frequency were discussed. 2. To implement the Dodge-Romig standardized sampling plan for incoming raw materials. 3. To document quality control procedures through a flow of forms, such as check sheets. This is to focus and optimize the quality control efforts of the company. Finally, areas for further study were identified such as quality function deployment study and the implementation of attribute charts.
Feasibility study
Keywords: Relay Electronics Corporation; Electronics industry; Quality control